How to deal with replaced common hepatic artery during laparoscopic pancreaticoduodenectomy - Zimmitti, Giuseppe; Manzoni, Alberto; Codignola, Claudio; Postiglione, Vittorio; Garatti, Marco; Rosso, Edoardo (Digestive Medicine Research; Vol 2 (March 2019): Digestive Medicine Research, 2019)
Replaced common hepatic artery (RCHA) constitutes a rare but serious anatomical variation of the hepatic artery during laparoscopic pancreaticoduodenectomy (PD). Hereby, we report a technique to deal with such a situation during laparoscopic PD for cancer.